2007
DOI: 10.1104/pp.107.106062
|View full text |Cite
|
Sign up to set email alerts
|

pSAT RNA Interference Vectors: A Modular Series for Multiple Gene Down-Regulation in Plants

Abstract: RNA interference (RNAi) is a powerful tool for functional gene analysis, which has been successfully used to down-regulate the levels of specific target genes, enabling loss-of-function studies in living cells. Hairpin (hp) RNA expression cassettes are typically constructed on binary plasmids and delivered into plant cells by Agrobacterium-mediated genetic transformation. Realizing the importance of RNAi for basic plant research, various vectors have been developed for RNAi-mediated gene silencing, allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 56 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, it also allowed easy modification and removal of the ATG-containing NcoI site from several pSAT-AFP and pSAT.pro.MCS.ter plasmids, allowing for greater versatility while cloning ATG-containing target genes into these vectors (Chung et al, 2005). Other modifications of the basic pSAT-AFP plasmids (Table I) included the introduction of the pSAT-BiFC family of plasmids, useful for the bimolecular fluorescence complementation assay (Citovsky et al, 2006), the construction of pSAT-red fluorescent protein (RFP), for the N-and C-terminal fusion of RFP (enhanced cyan variant of GFP-enhanced cyan fluorescent protein [ECFP], or the monomeric form of DsRed2; Chung et al, 2005;Citovsky et al, 2006), and the assembly of pSAT-RNAi, a set of vectors useful for the expression of hairpin structures for RNAi in plant cells (Dafny-Yelin et al, 2007). Additional plasmids, specifically designed to facilitate the expression of epitope-tagged proteins in plant cells, have also been constructed (T. Tzfira, unpublished data), as have two sets of plant selection-marker expression cassettes, controlled under two different constitutive promoters (Chung et al, 2005;Tzfira et al, 2005), allowing the user the freedom of choosing the preferred selection marker while assembling a multigene binary vector.…”
Section: The Psat Family Of Plasmidsmentioning
confidence: 99%
“…Furthermore, it also allowed easy modification and removal of the ATG-containing NcoI site from several pSAT-AFP and pSAT.pro.MCS.ter plasmids, allowing for greater versatility while cloning ATG-containing target genes into these vectors (Chung et al, 2005). Other modifications of the basic pSAT-AFP plasmids (Table I) included the introduction of the pSAT-BiFC family of plasmids, useful for the bimolecular fluorescence complementation assay (Citovsky et al, 2006), the construction of pSAT-red fluorescent protein (RFP), for the N-and C-terminal fusion of RFP (enhanced cyan variant of GFP-enhanced cyan fluorescent protein [ECFP], or the monomeric form of DsRed2; Chung et al, 2005;Citovsky et al, 2006), and the assembly of pSAT-RNAi, a set of vectors useful for the expression of hairpin structures for RNAi in plant cells (Dafny-Yelin et al, 2007). Additional plasmids, specifically designed to facilitate the expression of epitope-tagged proteins in plant cells, have also been constructed (T. Tzfira, unpublished data), as have two sets of plant selection-marker expression cassettes, controlled under two different constitutive promoters (Chung et al, 2005;Tzfira et al, 2005), allowing the user the freedom of choosing the preferred selection marker while assembling a multigene binary vector.…”
Section: The Psat Family Of Plasmidsmentioning
confidence: 99%
“…Wesley et al (2001) tested a variety of constructs of this type and found that the combination of doublestranded RNA, produced after splicing of the intron separating two identical but oppositely-oriented DNA fragments, was far more effective in gene silencing expression than either sense suppression (''co-suppression'') or traditional antisense constructs. Other groups (Dafny-Yelin et al 2007) have produced similar vector sets that contain RNAi elements, but again, these contain only constitutive promoters. We have built one constitutive RNAi cloning vector (plasmid J16), but otherwise, we focused on production of seed-specific plasmids, that will allow for specific silencing of certain types of genes (such as those involved in lipid metabolism) whose complete silencing throughout the plant may be deleterious.…”
Section: Discussionmentioning
confidence: 98%
“…In the years that followed, the auxillary vectors were improved by inclusion of various promoters and terminators (Chung et al 2005). Synthesis of plasmids containing fusion-compatible genes allowing for study of bimolecular fluorescence complementation (BiFC; Citovsky et al 2006), N-and C-terminalfusion compatible fluorescence proteins, and constitutive RNAi interference elements (Dafny-Yelin et al 2007) followed soon after. Other powerful methods have been described recently.…”
Section: Discussionmentioning
confidence: 99%
“…Then, dsRNA molecules are processed by a RNase III-like enzyme (dicer) into small interfering RNAs (siRNAs) of 21-23 nucleotides in length. Finally, siRNAs are recruited to the RNA induced silencing complex (RISC), which in turn mediates the cleavage of the target mRNA [2,3]. RNA silencing has been investigated in many plants.…”
Section: Introductionmentioning
confidence: 99%